The Implementation Of Self Regulated Learning Model To Improve The Technology Of Information And Communication Students’ Learning Results Class Of VIII A SMP Bhaktiyasa Singaraja At 2012/2013 Academic Year - Sudadiartharia, Komang (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2013)
This study were aimed at improving the technology of information andcommunication students’ learning results by applying Self Regulated Learning (SRL) type, and knowing students’ responses about SRL type implementation.Subjects of the study were the class VIII A students of SMP BhaktiyasaSingaraja at the first semester in the academic year 2012/2013, which involve 26 students. The design of this study was Classroom Action Research (CAR) that consists of two cycles. The data collected in this research is the result of learning and response against the implementation of SRL learning of model students in the subject of information technology and communication. Data of students learning results were collected using test and observation where as data of students responses were collected using questionnaire.The result of this study showed that (1) there are improvement of students’learning results. This was showed by amounts of classical success on the first cycle was about 65.38%, and on the second cycle was about 84.61%.The improvement of this learning results was about 19.23%. (2) the average amounts of students’ responses about SRL type implementation belong to positive responses that was about 43,92. Theresearcher concluded that the implementation of SRL type on technology of information and communication lesson was improved students’ learning result and got a positiveresponses.